Basics of animal communication : interaction, signalling and sensemaking in the animal kingdom - Martinelli, Dario (Cambridge Scholars Publishing, 2017)
This volume represents a short, yet systematic introduction to the topic of "animal communication", in a way that blends natural sciences and humanities into a multidisciplinary approach. It is structured in a way that allows students and teachers in this field to employ it as a useful pedagogical tool, and it is written with a style that is clear and engaging. A glossary of difficult terms and a rich bibliography are also available, altogether making Basics of Animal Communication very informative reading.